Frequency of Mismatch Repair Protein Deficiency in a Puerto Rican Population with Colonic Adenoma and Adenocarcinoma - REVERÓN, DAYANA (Cancer Genomics Proteomics, 2018)
Background/Aim: Microsatellite instability (MSI) results from genetic alterations involving the mismatch repair (MMR) genes MLH1, PSM2, MSH2, and MSH6. MSI has been implicated in both sporadic CRC and Lynch syndrome. The aim of the study was to assess the frequency of alterations in MMR protein expression in both primary colorectal cancer and precursor lesions among Puerto Rican patients. Patients and Methods: A retrospective study of 84 Puerto Rican patients was performed to assess the frequency of MMR protein expression alterations in both primary CRC and precursor lesions using tissue microarray and immunohistochemistry. Results: The loss of expression of both MLH1 and PMS2 proteins was present in 6.3% of adenomas, 9.1% of adenomas with high-grade dysplasia and 9.4% of colon adenocarcinomas. Negative nuclear staining for both MSH2 and MSH6 proteins was found in 2.4% of colon adenocarcinomas. Conclusion: When compared to prior reports, this study suggests a lower frequency of MSI among the Puerto Rican population. The higher prevalence of MLH1 mutations correlates with previous studies of protein expression among the Hispanic community including Colombian, Uruguay and Brazilian populations.